Pengaruh Kemampuan Koneksi Matematika Terhadap Hasil Belajar Siswa Pada Materi Garis Singgung Lingkaran Kelas VIII SMPN 2 Sumbergempol Tulungagung - Miftahul Azizah; fitria fauziyah (Program Studi Pendidikan Matematika UIN Raden Fatah Palembang, 2019)
The purpose of the research is to know whether there are influences between ability of mathematics connection with student learning result and also to know how huge the impact of that caused by both of variables. The research used quantitative approach, using pearson product moment correlation test as a test of the relationship between mathematical connection ability with student learning outcomes, before it used to has done normality test using kolmogorov-smirnov. First, took an instrument data first in the validity and reliability test. All of calculations start from valid and reliable tests to data analysis using 5% significance level was used SPSS v-16 software. The hypothesis test resulted in a significance of 0.001 less than 0.05 it means there are correlation between mathematical connection ability and student learning outcomes. The correlation value pearson product’s moment is 0.706 it means the relationships have strong category. Key word : Mathematics connection and Student learning result